TINJAUAN LITERATUR SISTEMATIS: PERAN MANAJEMEN SDM DALAM MENINGKATKAN KUALITAS DI ERA DIGITAL - Anissa Ayu; Muhammad Chaerul Rizky; Daud Arifin; Nur Aisyah; Larenza Dwiky Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to conduct a systematic literature review on the role of Human Resource Management (HRM) in improving organizational quality in the digital era. Key issues examined include the transformation of HR functions due to digitalization, the digital competency gap in the workforce, and the relevance of conventional HRM practices amid technological disruption. The method used is a Systematic Literature Review (SLR) focused on identifying research gaps from 17 scientific articles published between 2013 and 2025. Findings reveal four major gaps: (1) limited studies in developing country contexts, (2) insufficient holistic integration of HRM functions, (3) a scarcity of longitudinal studies, and (4) weak linkages between people analytics and measurable quality indicators. The novelty of this research lies in the systematic gap mapping connecting digital HRM dimensions with organizational quality indicators. Recommendations for future research include longitudinal quantitative studies and development of digital HRM-based quality measurement instruments in the Indonesian context